2020
DOI: 10.1002/nano.202000032
|View full text |Cite
|
Sign up to set email alerts
|

Magneto‐optic effect of two‐dimensional materials and related applications

Abstract: Magneto‐optic effect is attracting wide interest as it renders a contactless, potentially power‐free, highly sensitive and spatio‐temporal resolved way in both magnetic material characterization and light manipulation. Intensive explorations exhibit its potential in diverse applications such as optical communication, data storage, phase modulator, optical isolator, and magnetic‐field sensor. Noteworthy, atomically thin two‐dimensional (2D) materials represented by graphene demonstrate the interplay of large sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 131 publications
(178 reference statements)
0
33
0
Order By: Relevance
“…It is known that an external magnetic field breaks the time‐reversal symmetry in non‐magnetic materials, [ 9,10 ] leading to magneto‐optical Faraday and Kerr rotation effects. [ 11,12 ] Giant magneto‐optical Raman effects have also been observed in non‐magnetic InSe [ 13 ] and MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that an external magnetic field breaks the time‐reversal symmetry in non‐magnetic materials, [ 9,10 ] leading to magneto‐optical Faraday and Kerr rotation effects. [ 11,12 ] Giant magneto‐optical Raman effects have also been observed in non‐magnetic InSe [ 13 ] and MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the condition for the realization of transmitted interference colour, namely, 4nL > 400 nm cannot be satisfied in these systems according to the well-known Michel-Lévy chart. Considering the interplay between the shape anisotropy and optical/ magnetic anisotropy 18,[29][30][31][32] , magnetic two-dimensional (2D) materials with a wide optical bandgap offer excellent prospects for realization of a transparent hydrogel with engineerable interference colours, as their shape anisotropy shows two or three orders of magnitude larger than those of other dimensional systems.…”
mentioning
confidence: 99%
“…[ 133,139,192 ] The examples of magnetic materials that do exist in the 2D phase and attract a lot of interest are CrI 3 , [ 193 ] Fe 3 GeTe 2 , [ 194 ] CrGeTe 3 , Cr 2 Ge 2 Te 6 , [ 195 ] and FePS 3 . [ 133 ] An extensive review of magneto‐optic effects in 2D materials and related applications can be found in the study by Lan et al [ 196 ] Note that magnetic 2D materials are used either by themselves for a magneto‐optical response or in pair with other 2D or quasi 2D materials. For example, Figure 3d shows a heterostructure formed by an ultrathin ferromagnetic semiconductor CrI 3 and a monolayer of WSe 2 .…”
Section: Advanced Nonreciprocal Materials: Wss Metamaterials Magnetmentioning
confidence: 99%